2023
DOI: 10.1002/biot.202200644
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the topological flow transformations in an aerial vortex bioreactor with a floating washer

Igor V. Naumov,
Ruslan G. Gevorgiz,
Sergey G. Skripkin
et al.

Abstract: BackgroundResearch into the flow structure in an aerial vortex bioreactor is relevant for developing the methods for growing cell cultures. Determining the optimal cultivation condition for a certain process is especially important in the case when such parameters of the medium as density and viscosity significantly change with the culture growth in the bioreactor.Methods and resultsThe research of the flow dynamic was carried out in an 8.5 L universal aerial vortex bioreactor, with a washer freely floating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[75] It was demonstrated that decreasing light supply from 20 to 10 sm increased biomass accumulation by three times and nitrogen and phosphorus recovery rates by almost 2.5 times. [52] In the majority of bioreactors, light supply, [50][51][52]81] cell concentration, [82][83][84] CO 2 concentration, [85,86] pH, [87][88][89][90][91] temperature, [52,92] concentration of nutrients, [91] and other parameters are affected by and have an impact on the growth of microorganisms. [89,91,[93][94][95] These systems must be monitored and externally maintained to achieve optimal results [85,95] which adds to the overall cost.…”
Section: Photobioreactor Design Is Pivotal For High Yield Of Microalgaementioning
confidence: 99%
“…[75] It was demonstrated that decreasing light supply from 20 to 10 sm increased biomass accumulation by three times and nitrogen and phosphorus recovery rates by almost 2.5 times. [52] In the majority of bioreactors, light supply, [50][51][52]81] cell concentration, [82][83][84] CO 2 concentration, [85,86] pH, [87][88][89][90][91] temperature, [52,92] concentration of nutrients, [91] and other parameters are affected by and have an impact on the growth of microorganisms. [89,91,[93][94][95] These systems must be monitored and externally maintained to achieve optimal results [85,95] which adds to the overall cost.…”
Section: Photobioreactor Design Is Pivotal For High Yield Of Microalgaementioning
confidence: 99%